2012
DOI: 10.1038/nature11312
|View full text |Cite
|
Sign up to set email alerts
|

Activation of specific interneurons improves V1 feature selectivity and visual perception

Abstract: Inhibitory interneurons are essential components of the neural circuits underlying various brain functions. In the neocortex, a large diversity of GABAergic interneurons have been identified based on their morphology, molecular markers, biophysical properties, and innervation pattern1,2,3. However, how the activity of each subtype of interneurons contributes to sensory processing remains unclear. Here we show that optogenetic activation of parvalbumin-positive (PV+) interneurons in mouse V1 sharpens neuronal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
527
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 559 publications
(580 citation statements)
references
References 35 publications
46
527
7
Order By: Relevance
“…For example, Atallah, et al (2012) found that optogenetically activating PV interneurons decreased pyramidal cell activity divisively by a factor of 1.4 and subtracted a constant amount. Another optogenetic study found that activating PV inhibitory interneurons sharpened the orientation tuning and direction selectivity of the nearby pyramidal cells to which they were directly connected (Lee, et al, 2012b). In contrast to the findings of Wilson et al (2012), the sharpening was specifically due to PV interneurons because activating SOM and VIP inhibitory interneurons had no such effect.…”
Section: Modulation That Suppresses Responses To Rf Inputmentioning
confidence: 55%
See 1 more Smart Citation
“…For example, Atallah, et al (2012) found that optogenetically activating PV interneurons decreased pyramidal cell activity divisively by a factor of 1.4 and subtracted a constant amount. Another optogenetic study found that activating PV inhibitory interneurons sharpened the orientation tuning and direction selectivity of the nearby pyramidal cells to which they were directly connected (Lee, et al, 2012b). In contrast to the findings of Wilson et al (2012), the sharpening was specifically due to PV interneurons because activating SOM and VIP inhibitory interneurons had no such effect.…”
Section: Modulation That Suppresses Responses To Rf Inputmentioning
confidence: 55%
“…In contrast to the findings of Wilson et al (2012), the sharpening was specifically due to PV interneurons because activating SOM and VIP inhibitory interneurons had no such effect. Lee, et al (2012b) showed the relevance of these effects to perceptual discrimination as measured psychophysically by activating PV interneurons in awake mice. They found that the improvement that this produced in orientation discrimination mirrored the sharpened V1 orientation tuning as measured electrophysiologically.…”
Section: Modulation That Suppresses Responses To Rf Inputmentioning
confidence: 99%
“…1 However, the dopamine dysregulation hypothesis does not explain cognitive deficits and negative symptoms. The current view, beside a dysregulation of the dopaminergic system, also incorporates misbalanced glutamatergic and GABAergic (Gamma-aminobutyric acid) neurotransmitters (Marsman et al, 2013) 2 mediating cortical processing (pyramidal cells/interneurons) and supporting the notion of aberrant sensory processing (Lee et al, 2012;Lewis, 2014). In fact, interactions of glutamatergic NMDAR (N-Methyl-D-Aspartate receptor) and dopamine receptors are a key mechanism in multiple pathophysiological theories of schizophrenia (Frohlich & Van Horn, 2014 Q5 ).…”
Section: Schizophreniamentioning
confidence: 78%
“…Furthermore, by setting a narrow window of spiking FSIs can synchronize the neuronal activity and generate high frequency cortical rhythms [65][66][67]. Finally, by directly projecting to the soma of the neurons, FSIs control the effective gain of the neurons and provide the much needed divisive inhibition and a mechanism of normalization [68][69][70]. In the striatum despite their high firing rates, FSIs do not seem to play a major role in controlling the firing of MSNs [35] and so far it has not been possible to attribute a functional role to FSIs in the striatum.…”
Section: Discussionmentioning
confidence: 99%